The Correlation between Blood Lead Level with Hypertension of Painting Cars Worker in Surabaya - Hendra Eka (JURNAL KESEHATAN LINGKUNGAN, 2017)
Lead (Pb) is a metal that used as a color pigment in paint material. Lead has an acute effect on blood pressure and caused hypertension in chronic poisoning because it accumulated in blood. The objective of this research was to identify the correlation between aerial lead level and blood lead level with hypertension of workers in car painting workshop Surabaya. This research was an observational with cross-sectional study and to know the correlation analyzed by using phi correlation. Sample of this research were 16 respondents taken from population compatible from deï¬ ned criteria. Blood lead level and blood pressure examined by the health workers then analyzed in the laboratory and using questionnaires to determine the characteristic of respondents. The results of this research is 83.33% respondents were exposed have blood lead concentration exceeds the limit that is > 10 Î¼g/dL and 66.67% respondents were exposed have hypertension. Blood lead concentration have a strong correlation with hypertension (r = 0.618). The workers need to do a routine blood lead concentration check up once every 6 months and use personal protective equipment at work, consume foods and beverages that contain high calcium often nevertheless decrease smoking habit to inhibit absorption of lead in blood.